Role of Cortical Mastoidectomy in the Management of Safe Chronic Otitis Media - Verma, Lok Ram; Paudel, Dhundi Raj (Journal of Nepalgunj Medical College, 2020)
Introduction: Role of cortical mastoidectomy in tympanoplasty for Chronic Otitis Media Mucosal inactive disease is controversial. Some arguments are in favor and suggest that cortical mastoidectomy increases the air reservoir in the mastoid and also help in achieving the patency of aditus but others believe that the ingrowths of squamous epithelium, potential for injury to the inner ear structures and facial nerve during mastoid surgery outweighs the beneficial effects on tympanic membrane healing. Aims: To assess the hearing improvement and graft uptake in patients undergoing Tympanoplasty and Tympano-mastoidectomy in chronic otitis media mucosal inactive disease. Methods: This was a comparative study comprises of 50 patients with Chronic Otitis Media Mucosal inactive ear, conducted in the patients attending the department of ENT in NGMC teaching hospital from Nov 2017 to May 2019. All cases were operated during a period of one half year. 25 patients were selected for tympanoplasty (Group A) and 25 patients were selected for Tympanoplasty with cortical mastoidectomy (Group B). Results: There were 14(28%) male and 36(72%) female, with mean age of 28. 36 years, ranging from minimum of 13 years to maximum 56 years. The postoperative audiograms were recorded after 3 months. Type I tympanoplasty with cortical mastoidectomy has better graft uptake (96%) as compared to without mastoidectomy (84%). Post-operative hearing improvement is almost equal in tympano-mastoidectomy (13.24 dB) and tympanoplasty (13.04 dB). Conclusion: Post-operative hearing gain almost equal in both study group but graft uptake was better with tympano-mastoidectomy then tympanoplasty alone in present study.